Structural dynamic properties of reinforced concrete tunnel form system buildings. (July 2022) - Hadzima-Nyarko, Marijana; Ademović, Naida; Koković, Veljko; Lozančić, Silva
Abstract: Tunnel form buildings refer to reinforced concrete structures constructed using the tunnel formwork system, which results in a repetitive concrete cellular structure composed only of walls and flat slabs. This widespread low-cost and robust system reaches its popularity for residential buildings in the 70 s and 80 s of the last century. At the time of their design, a 3D finite element analysis has not been conducted. The seismic design relied on building codes that provide approximate fundamental period formula, which commonly depends on structural system type (shear wall, frame), material (steel, reinforced concrete), and the building height. Based on the existing RC tall buildings, both modeling and vibration measurements were carried out to provide a detailed case study as well as to increase the knowledge base of existing buildings frequencies of vibration. The fundamental vibration period obtained from numerical analyses of three real reinforced concrete shear walls buildings (RCSW) located in the Croatian city Osijek, were compared with values obtained using the formulas in the European code EN1998-1:2004 (CEN 2004) and other available literature. Numerical modeling is performed using SAP2000 software. The objectives of the article are experimental identification of the dynamic characteristics (mainly natural frequency) of existing Tunnel form buildings, as well as comparison with values obtained by approximate formulas and a detailed structural model. The results of this study showed a very good agreement between the numerical 3D model and the experimental campaign conducted with the usage of ambient testing. Nevertheless, a serious question arises regarding the confidence of proposed empirical formulas provided in the codes and standards which may lead to imprecise and false results.